1992
DOI: 10.1002/jnr.490310319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acidic fibroblast growth factor on higpocampal long‐term potentiation in fasted rats

Abstract: Effects of human recombinant acidic fibroblast growth factor (haFGF) on long-term potentiation (LTP) and the increase of the spike amplitude induced by weak tetanic stimulation were investigated and compared with those of CS23 (modified human basic FGF) in the dentate gyrus of fasted and nonfasted rats. haFGF didn't influence the LTP induced by the tetanus of 100 pulses at 100 Hz in both 24 hr fasted and non-fasted rats. On the other hand, the tetanus of 20 pulses at 60 Hz significantly enhanced the amplitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…However, after administration of HFS, FGL was found to facilitate both PTP and LTP up to 3 h post-HFS in the anesthetized rat and up to 24 h post-HFS in the awake rat. Although FGL is likely to stimulate the FGFR differently than the FGFs molecules (Hinsby et al 2004a,b;Kiselyov et al 2005) and may act also on other receptors, this result corroborates the investigation of Zhao and colleagues reporting a severe impairment of in vitro MPP-LTP in the Fgfr1 conditional knock-out mouse (Zhao et al 2007) and an earlier study showing that icv injection of human acidic FGF facilitates the generation of LTP by a weak tetanus in the awake rat (Hisajima et al 1992). Interestingly however, a recent study reports that FGL alleviated the deficiency in LTP displayed by aged rats, but had no effect on LTP 1 h post-induction in young Wistar rats in vivo (Downer et al 2010).…”
Section: Discussionsupporting
confidence: 85%
“…However, after administration of HFS, FGL was found to facilitate both PTP and LTP up to 3 h post-HFS in the anesthetized rat and up to 24 h post-HFS in the awake rat. Although FGL is likely to stimulate the FGFR differently than the FGFs molecules (Hinsby et al 2004a,b;Kiselyov et al 2005) and may act also on other receptors, this result corroborates the investigation of Zhao and colleagues reporting a severe impairment of in vitro MPP-LTP in the Fgfr1 conditional knock-out mouse (Zhao et al 2007) and an earlier study showing that icv injection of human acidic FGF facilitates the generation of LTP by a weak tetanus in the awake rat (Hisajima et al 1992). Interestingly however, a recent study reports that FGL alleviated the deficiency in LTP displayed by aged rats, but had no effect on LTP 1 h post-induction in young Wistar rats in vivo (Downer et al 2010).…”
Section: Discussionsupporting
confidence: 85%
“…injections of FGF-1. LTP can be induced using a subthreshold stimulation in combination with administration of FGF-1; however, LTP cannot be induced using the subthreshold stimulation alone (Hisajima et al 1992). Further evidence came from a study using an FGF-1 fragment analog (amino acid residues 1 through 29 of FGF-1 with an alanine substituted at position 16) on accelerated senescence-prone mice.…”
Section: Learning and Memorymentioning
confidence: 98%
“…A similar model system demonstrating growth factor effects on LTP is provided by the following example: Transection of the fimbria-fornix pathway decreases the frequency of LTP generation. Intracerebroventricular injection of epidermal growth factor (EGF) or FGF-2 facilitated LTP generation in the fimbria-fornix lesioned rats, suggesting that EGF and FGF-2 can improve hippocampal LTP impairment after loss of subcortical afferents (Abe et al 1992). …”
Section: Learning and Memorymentioning
confidence: 99%
“…, 2004; Sanchez‐Heras et al. , 2006) and a number of studies have shown that FGFR and NCAM are involved in learning and memory consolidation (Hisajima et al. , 1992; Cremer et al.…”
Section: Introductionmentioning
confidence: 99%